2021
DOI: 10.3389/fnagi.2021.731332
|View full text |Cite
|
Sign up to set email alerts
|

Gait-Related Brain Activation During Motor Imagery of Complex and Simple Ambulation in Parkinson's Disease With Freezing of Gait

Abstract: Background: Freezing of gait (FOG) in Parkinson's disease (PD) is a devastating clinical phenomenon that has a detrimental impact on patients. It tends to be triggered more often during turning (complex) than during forwarding straight (simple) walking. The neural mechanism underlying this phenomenon remains unclear and requires further elucidation.Objective: To investigate the differences in cerebral functional magnetic resonance imaging responses between PD patients with and without FOG during explicitly vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…In particular, reduced activity in the CLR and the right GP was detected during imagined gait in PD patients with FoG than PD patients without FoG ( Peterson et al, 2014a ). In contrast, other MI studies comparing imagined gait between PD patients with FoG and without FoG reported abnormal activity increases in several locomotor regions ( Huang et al, 2021 ) that positively correlated with disease duration in the PD patients with FoG. Moreover, increased activation in the MLR was positively correlated with FoG severity ( Snijders et al, 2011 ).…”
Section: Task-based Imaging Studies Of Fog In Parkinson’s Diseasementioning
confidence: 80%
See 2 more Smart Citations
“…In particular, reduced activity in the CLR and the right GP was detected during imagined gait in PD patients with FoG than PD patients without FoG ( Peterson et al, 2014a ). In contrast, other MI studies comparing imagined gait between PD patients with FoG and without FoG reported abnormal activity increases in several locomotor regions ( Huang et al, 2021 ) that positively correlated with disease duration in the PD patients with FoG. Moreover, increased activation in the MLR was positively correlated with FoG severity ( Snijders et al, 2011 ).…”
Section: Task-based Imaging Studies Of Fog In Parkinson’s Diseasementioning
confidence: 80%
“… Cross-sectional Correlational (direct with motor arrests) Turning: lower BOLD in left premotor area & left SPL, and higher BOLD in bilateral IFG (C/T FoG-). Higher FC in FoG + between bilateral MLR, left GPi & bilateral MLR, and right GPi & left STN (C/T walking) Interference Huang et al, (2021) 22 FoG+ 15 FoG- 15 HC OFF H&Y, LEDD, MMSE, PDQ-39, UPDRS-III, VMIQ, new FoG-Q and 50 m walking test. Activation (BOLD) ROI (MLR, CLR, SLR) MI paradigm: first person video-guided gait imagery of normal gait (walking and 360 degrees turning) vs FoG gait (FoG walking and FoG turning).…”
Section: Task-based Imaging Studies Of Fog In Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The superior occipital gyrus is one of the key regions in the visual association cortex responsible for higher level visual association processing and interpreting visual images ( Alves et al, 2012 ). A recent video-guided motor imagery study found that PD-FOG showed increased activity in the superior occipital gyrus than PD-NFOG when watching the video clips of FOG turning ( Huang et al, 2021 ). The finding implied that superior occipital gyrus might occupy a special role in enhancing spatiotemporal demands in gait generating.…”
Section: Discussionmentioning
confidence: 99%
“…In Parkinsonian (PD) patients, motor imagery of gait in gait freezers improved gait velocity, stride length, stance time, swing time, single support time, and total double support time [ 43 ]. Dynamic Neuro-Cognitive Imagery (DNI™)—a codified method for imagery training—improved balance, walking, mood, and coordination, and patients felt more physically and mentally active [ 44 ].…”
Section: Functional Equivalence Between Imagery and Perception/action...mentioning
confidence: 99%